2011
DOI: 10.3109/03630269.2011.588140
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Capillary Electrophoresis and High Performance Liquid Chromatography for Detection and Quantification of Hb Constant Spring [Hb CS; α142, Term→Gln (TAA>CAA IN α2)]

Abstract: Hb Constant Spring [Hb CS; α142, Term→Gln (TAA>CAA in α2)] is often missed by routine laboratory testing since its mRNA as well as gene product are unstable and presented at a low level in peripheral blood. This study aimed to analyze the efficacy of capillary electrophoresis (CE) and high performance liquid chromatography (HPLC) for detecting and quantifying Hb CS in 19 heterozygotes and 14 homozygotes with Hb CS as well as 10 Hb H-CS disease subjects who were detected by molecular analysis. In the CE electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 12 publications
3
12
1
Order By: Relevance
“…In contrary with the current study, Hb CS heterozygotes carrying Hb E, another unstable hemoglobin variant of the b-globin chain which is frequently found in the Thai population, can be detected by CE but not by HPLC. Consistent with the previous study, the CE had higher sensitivity than HPLC for detection of Hb CS [16]. Thus, CE analysis is necessary in a couple which is discordant for thalassemia that is one partner has a-thalassemia-1 and the other has b-thalassemia or Hb E trait.…”
Section: Discussionsupporting
confidence: 81%
“…In contrary with the current study, Hb CS heterozygotes carrying Hb E, another unstable hemoglobin variant of the b-globin chain which is frequently found in the Thai population, can be detected by CE but not by HPLC. Consistent with the previous study, the CE had higher sensitivity than HPLC for detection of Hb CS [16]. Thus, CE analysis is necessary in a couple which is discordant for thalassemia that is one partner has a-thalassemia-1 and the other has b-thalassemia or Hb E trait.…”
Section: Discussionsupporting
confidence: 81%
“…CE was performed in completely automatic equipment (Cebia-Model 2007). Control samples were prepared using a mixture of Hbs A, F, S and C and included in each experiment alongside the test samples [18].…”
Section: Methodsmentioning
confidence: 99%
“…Samples on Guthrie cards were stored at -20 o C with dessicant material to keep specimens dry. CE-HPLC was used as a confirmatory test after Capillary electrophoresis [18]. Guthrie card samples were analyzed, using CE-HPLC [19].…”
Section: Methodsmentioning
confidence: 99%
“…Whether the CE, which has proven superior to the HPLC in the detection of Hb constant spring [Hb CS; a142, Term ? Gln (TAA [ CAA IN a2)] trait [7], could diagnose the co-inheritance of Hb Hope and Hb CS is unclear. In this study, we reported the CE electrophoregram of the samples with co-inheritance of Hb Hope and Hb CS.…”
Section: Introductionmentioning
confidence: 99%